RUU PERTANAHAN: ANTARA MANDAT DAN PENGINGKARAN TERHADAP UUPA 1960 - Gunawan Gunawan (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2014)
The sense of agrarian term covers the surface of the earth (land ). The land law ought to refer to the agrarian law. Theplanning of land constitution should also refer to the Constitution No. 5, 1960 on Basic Agrarian Law. Whether the planningof land constitution opposes the Basic Agrarian Law can be verified by the question on how far the above planning is made.This was mandated by the Basic Agrarian Law.Keywords: land law, right on land, land jurisdiction